Human Immune System Mice for the Study of Human Immunodeficiency Virus-Type 1 Infection of the Central Nervous System - Evering, Teresa H.; Tsuji, Moriya (Frontiers in Immunology, 2018)
Immunodeficient mice transplanted with human cell populations or tissues, also known as humanized immune system (HIS) mice, have emerged as an important and versatile tool for the in vivo study of Human Immunodeficiency Virus-1 (HIV-1) pathogenesis, treatment and persistence in various biological compartments. Recent work in HIS mice has demonstrated their ability to recapitulate critical aspects of human immune responses to HIV-1 infection and such studies have informed our knowledge of HIV-1 persistence and latency in the context of combination antiretroviral therapy (cART). The central nervous system (CNS) is a unique, immunologically privileged compartment susceptible to HIV-1 infection, replication and immune-mediated damage. The unique, neural, and glia-rich cellular composition of this compartment, as well as the important role of infiltrating cells of the myeloid lineage in HIV-1 seeding and replication makes its study of paramount importance, particularly in the context of HIV-1 cure research. Current work on the replication and persistence of HIV-1 in the CNS as well as cells of the myeloid lineage thought to be important in HIV-1 infection of this compartment have been aided by the expanded use of these HIS mouse models. In this review, we describe the major HIS mouse models currently in use for the study of HIV-1 neuropathogenesis, recent insights from the field, limitations of the available models and promising advances in HIS mouse model development.